AKTIVASI DAN KARAKTERISASI BENTONIT-H - Toeti Koestiari1, ; Amiruddin Prawita2, (Matematika dan Sains, 2009)
The research was conducted to compare the bentonit-H structures activated at temperature of 40 oC, 100 oC, and 300 oC with the time heating of 1, 2, and 3 hours, respectively. Its phsycochemical properties was measured using the infrared spectrophotometer, while the basal spacing was determined by XRD. The infrared spectra of activated bentonit-H showed the similarity at all wave number, but the value of %T was different. The maximum intensity indicated the similarity at 2 ? = 19,78576 o and 26,64257o so there are the small different of basal spacing. The bentonit-H heated at temperature of 40oC for 3 hours has opportunity to activated using the other method.